Efficacy of a neuroscience informed psychoeducation intervention on cognitive, emotional, and substance use outcomes in college students: a pilot study - Rezapour, Tara; McLean, Kayla L.; Psederska, Elena; Chokshi, Swara; Maleki, Khashayar Niki; Ekhtiari, Hamed; Vassileva, Jasmin (Frontiers in Psychiatry, 2025)
IntroductionDespite revolutionary advances in understanding the neurobiology of substance use, these insights have not been translated into effective prevention or intervention programs. To address this gap, we developed Neuroscience-Informed Psychoeducation for Addiction (NIPA), a mobile app designed to enhance metacognitive awareness, increase cognitive resilience, and promote neurocognitive skills for stress coping and substance misuse prevention. NIPA targets key cognitive functions—attention, memory, cognitive flexibility, and decision-making —by integrating neuroscience-based psychoeducation with gamified neurocognitive tasks and metacognitive training to enhance engagement and real-life application.ObjectiveIn this study, we aimed to examine whether using a neuroscience-based approach could change young adults’ attitudes and intentions to use drugs and alcohol, and improve their executive functions, emotional health, and decision-making.MethodSixty-eight undergraduates from a large urban public university participated in this pilot study. Eligibility criteria included: age ≥18, prior alcohol/tobacco/cannabis/other drug use, and ability to download and complete the app. Prior to the intervention, participants completed self-report cognitive, emotional, and substance use questionnaires; these were repeated after completing four 20-minute-long NIPA sessions. NIPA incorporates metacognitive training and game-based neurocognitive tasks delivered through cartoons, animations, and videos to increase awareness about the effects of drugs and alcohol on brain and cognition. Pre–post intervention changes were analyzed using Wilcoxon signed-rank and binomial tests.ResultsFindings reveal significant reductions from pre- to post-intervention assessment in self-reported deficits in executive function (Z=-7.11; p<0.001) and emotional distress including depression (Z=-2.58; p=0.010) and anxiety (Z=-2.49; p=0.013), and an increase in metacognitive awareness (Z=-3.07; p=0.002). Additionally, assessment of decision-making revealed reduced delay discounting of large magnitude rewards (Z=-2.11; p=0.035) and increased probability discounting of small probabilities (Z=-3.177; p=0.001), indicating increased sensitivity to uncertainty. Finally, participants reported significantly lower intentions to use and lower actual use of nicotine and cannabis, and lower binge drinking from pre- to post-intervention assessment.ConclusionThese preliminary results support the potential of NIPA as an effective tool for increasing metacognitive awareness and enhancing cognitive resilience against stress and uncertainty. Future studies with larger samples, including a control group and follow-up assessments, are required to support these findings and assess the long-term effects of the intervention.